PERANAN INDUSTRI PENGOLAHAN KRIPIK ”TEMPE GETI” DALAM MENGGERAKKAN PEREKONOMIAN DAERAH NGAWI - Dedy Kunhadi; Wulandari Harjanti (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
Family income can be added through a manufacture industry e.g. Kripik Tempe Geti. The purpose of this article is to analyze the process of Kripik Tempe Geti business advisability and the role of Kripik Tempe Geti industry in the territory economy. This research was held in Ngawi on 2007. The collecting data is done by intensive interview to the Kri[pik Tempe Geti industry. The data collected was analyzed in a descriptive quantitative. The analysis shows that Keripik Tempe Geti industry has a big chance to be expanded. The process of Kripik Tempe Geti is suitable done by score Benefit/Cost at 0.62 ratio. As seen from the growth of territory economy, Kripik Tempe Geti industry has given working chance for the people in Ngawi, just like from the supplying of the row material, production process, or from the marketing side. The increase of the household income from Kripik Tempe Geti industry reach out at 2,064,375 Rupiahs per months, besides it also can increase the income of the market doer such as motorcycle driver (ojek) or food small shop.